POSSIBLE INFLUENCES OF CORE PROCESSES ON THE EARTH'S ROTATION AND THE GRAVITY FIELD - Greiner-Mai H.; Jochmann H.; Barthelmes F.; Ballani L. (My University, 2003)
In this work, we review the processes in the Earth's core that influence the Earth's rotation on the decadal time scale. While core-mantle coupling is likely to be responsible for the decadal length-of-day variations, this hypothesis is controversial with respect to polar-motion variations. The electromagnetic-coupling torques are strongly dependent on the assumed electrical conductivity of the lower mantle, while the topographic torques are influenced by the topography of the core-mantle boundary (CMB). Because no comprehensive theoretical framework for determining the topographic and material parameters of the CMB region is currently available, the modeled results about the coupling torques can only be verified by their consistency with the observed variations of the Earth's rotation and the geomagnetic field. A second path of investigation is to consider the relative angular momentum of the core. Recently, the axial angular-momentum balance has been found to coincide with observed variations in the geomagnetic field and the length of day. However, with respect to polar-motion variations, the angular-momentum balance is not yet closed. We also discuss the role of an irregular motion of the figure axis of the oblate inner core with respect to the outer core and mantle in the excitation of polar motion. In particular, we assume that the associated changes of the Earth's inertia tensor cause the observed decadal variations in polar motion. From this assumption, we can derive the temporal variation of the orientation of the figure axis of the inner core from polar-motion data. Finally, we calculate the gravity variations caused by this relative inner-core motion and compare them with the accuracy of current and planned satellite missions.